Content selection in undergraduate LIS education - Zins, Chaim; Santos, Placida L. V. A. C. [UNESP] (Springer Nature, 2016)
The study presented in this article is aimed to improve the academic education in the field of library and information science by structuring the curricular and pedagogical reasoning that shapes the contents of undergraduate academic programs It was composed of two methodological phases The first phase was a systematic Critical Delphi study with 21 leading information science scholars from Brazil The second phase was an unsystematic formative evaluation of the content categories The evaluation was based on a Grounded theory study of more than 100 programs worldwide The study resulted in a universal model that sets the guiding principles for developing bachelor’s degree programs applicable worldwide The model, which is actually composed of two complementary models, is a systematic four step developing process (model1 1) and a structured plan of 288 content categories (model1 2) It is grounded on theoretical foundations and empirical studies.